The Aspiration of Black Mathematicians Women in Gaining Equality towards Male Domination in the Movie “Hidden Figures” (2016) - Salsabila, Davina; Priyoto, priyoto; Susiyati, Susiyati (JELL (Journal of English Language and Literature) STIBA-IEC Jakarta, 2025)
The aims of this research is to investigate the representation of gender roles in the film Hidden Figures (2016) through the authentic experiences of three African American women, Katherine Johnson, Dorothy Vaughan, and Mary Jackson who were employed at NASA in the 1960s. Using Gender Role Theory, this study examines the methods these characters use to confront and navigate discrimination in a workplace characterized by male dominance and racial segregation. Using qualitative content analysis methodology, this study focuses on specific scenes that illustrate the challenges these women face as a result of their race and gender. The results show that each character faces systemic barriers, including limited access to education, inadequate recognition, and exclusion from leadership roles. However, their resilience and determination allow them to overcome these barriers. Katherine asserts her right to participate in important meetings, Dorothy teaches herself programming to maintain her relevance in the evolving workforce, and Mary defies legal barriers to pursuing a career as an engineer. This representation emphasizes the film’s core message: that perseverance and self-respect can effectively challenge and resist oppressive gender norms. Ultimately, this research not only depicts the personal struggles of these women, but also highlights the broader societal implications of challenging conventional gender roles, underscoring the importance of visibility.